Immobilization of Iron Minerals on a Layered Silicate for Enhancing its Solar Photocatalytic Activity toward H2 Production - El-Hosainy, Hamza; Tahawy, Rafat; Esmat, Mohamed; El-Kemary, Maged; Ide, Yusuke (Frontiers in Energy Research, 2021)
The development of efficient and cost-effective solar photocatalysts capable of producing hydrogen from formic acid as a hydrogen storage medium is still a challenging issue. Herein, we report that iron minerals, ferric iron hydroxy sulfates (FHS), immobilized on a natural layered silicate, magadiite, can be used as a photocatalyst to produce hydrogen from formic acid under irradiation with solar simulator. The material exhibits the hydrogen production rate of 470 μmol g−1 h−1, which is considerably higher than that obtained on other iron minerals and comparable to that obtained on precious metal-based photocatalyst ever reported. The present result may open a way to design efficient photocatalyst for hydrogen production from formic acid in an economically and environmentally friendly way.